Indentification of moisture: nanoparticles in the butter submicrostructure - Rashevska, Tamara; Gulyy, Ivan; Pryadko, Nikolai; Nishchenko, M.; Lihtorovich, S. (My University, 2001)
By means of the elcectron microscopy study of the butter samples obtained by freezing-and-cleavage teehnique we have shown that their submicrostructure contains spherical particles, 2 to 100 nm in diameter, which can also aquire anisotropic shapes. За допомогою електронно-мікроскопічного дослідження зразків вершкового масла, отриманих методом заморожування та розщеплення, ми показали, що їхня субмікроструктура містить сферичні частинки діаметром від 2 до 100 нм, які також можуть набувати анізотропної форми.
Keywords: butter; submicrostructure; moisture; вершкове масло; субмікроструктура; кафедра теплоенергетики та холодильної техніки; кафедра технології молока і молочних продуктів